The identity of Doronicum calotum (Asteraceae, Senecioneae) - Fei, Wen-Qun; Wu, Xing; Ren, Chen; Chen, You-Sheng (Phytotaxa, 2019)
Doronicum calotum is revealed to be conspecific with D. gansuense and is an earlier name for the taxon. Doronicum gansuense is thus reduced to synonymy. Lectotype is designated for D. calotum.